Efektivitas Pengawasan Dinas Perindustrian dan Perdagangan Kabupaten Tabanan dalam Pengelolaan Pasar Tradisional Dauh Pala Kecamatan Tabanan, Kabupaten Tabanan - Ni Made Susantiasih; I Ketut Sukantha Artha Wibawa (Jurnal Widya Mahavira, 2025)
This study examines the effectiveness of supervision conducted by the Department of Industry and Trade of Tabanan Regency in managing the Dauh Pala Traditional Market, located in Tabanan District, Tabanan Regency. The study employed a qualitative research approach with a descriptive observational design and utilized purposive sampling techniques. The indicators used to assess supervisory effectiveness included accuracy, centralization, timeliness, flexibility, and guidance-oriented operational characteristics. Data were collected through field surveys, in-depth interviews, and literature review. The findings reveal that supervision at the Dauh Pala Traditional Market has not yet been effective based on the established indicators. Several unresolved issues remain, primarily due to obstacles faced by the Department of Industry and Trade of Tabanan Regency, including inadequate facilities and infrastructure, as well as insufficient budget allocation. This study suggests that supervisory activities should be conducted more consistently rather than limited to weekly or incidental inspections. In addition, supervisory officers should provide continuous guidance to traders, particularly those with rigid mindsets, to foster a culture of orderliness and cleanliness. Enhancing supervisory facilities, such as increasing the availability of motor vehicles, is also recommended to support more effective supervision.